Pengembangan Simrs Pasien Rawat Inap Obsgyn Di Bangsal AnisaRumah Sakit PKU Muhammadiyah Karanganyar - SRI LESTARI, WITDIYASTUTI; , Sri Darnoto S.KM M.PH; , Arief Kurniawan NP, SKM, M.PH (2015)
Anisa room and medical records unit at PKU Muhammadiyah Karanganyar Hospital use semi manual system where at registration, pharmacies and cashier have used computer based system but it is only limited access to services, but it is not integrated yet with the ward . There are 7 ward to inpatient in PKU Muhammadiyah Karanganyar Hospital, one of them is anisa ward, in anisa ward, the writing of patient identify is still manual. Most of anisa ward occurs the delays of recording and reporting patient to part of medical record and part of the management hospital. The purpose of this research is to design DFD, the data base, ERD, design of display system and do the trial system. The kind of this research is the study of research and development with the qualitative approach. The method of system development is prototype. In this research the technique of data collection use observation, interview, and documentation study. The sample of research are 8 person that consist of 2 registration officer, 2 ward anisa officer, 2 medical record officer, 2 IT officer. The sample of collection technique use purposive sampling. The development system use delphy 6 with the MySQL data base. The result of identification user, the researcher design 5 data flow diagram (DFD): there are DFD diagram cortex, DFD system that is designed, DFD recording patient registration, DFD recording services data, DFD recording and reporting, and Entity relationship diagram (ERD). The 10 table of data base and design interface system, input: 5 (user data, patient data, visit data, anamnesis data and partograph), and output: 5 (visit report, childbirth action report, gynecology report, death neonatal and maternal report).